SERT-Deficient Mice Fed Western Diet Reveal Altered Metabolic and Pro-Inflammatory Responses of the Liver: A Link to Abnormal Behaviors - Raymond Cespuglio; Anna Gorlova; Konstantin Zabegalov; Kirill Chaprov; Evgeniy Svirin; Kseniia Sitdikova; Alisa Burova; Boris Shulgin; Ksenia Lebedeva; Alexei V. Deikin; Sergey Morozov; Tatyana Strekalova (Frontiers in Bioscience-Landmark)
Background: The inheritance of the short SLC6A4 allele, encoding the serotonin transporter (SERT) in humans, increases susceptibility to neuropsychiatric and metabolic disorders, with aging and female sex further exacerbating these conditions. Both central and peripheral mechanisms of the compromised serotonin (5-HT) system play crucial roles in this context. Previous studies on SERT-deficient (Sert-/-) mice, which model human SERT deficiency, have demonstrated emotional and metabolic disturbances, exacerbated by exposure to a high-fat Western diet (WD). Growing evidence suggests the significance of hepatic regulatory mechanisms in the neurobiology of central nervous system disorders, supporting the ‘liver-brain’ concept. However, the relationship between aberrant behavior and hepatic alterations under conditions of SERT deficiency remains poorly investigated. Methods: One-year-old female Sert-/- mice and their wild-type (WT) littermates were subjected to a control diet (CD) or the WD for a duration of three weeks. The WD had a higher caloric content and was characterized by an elevated saturated fat content (21%) compared to the CD (4.5%) and contained 0.2% cholesterol. Mice were evaluated for anxiety-like behavior, exploration and locomotor activity in the open field test, as well as glucose tolerance and histological indicators of hepatic steatosis. Hepatic pro-inflammatory and metabolism-related gene expression and markers of nitrosative stress, were analyzed utilizing real-time polymerase chain reaction (RT-PCR) and correlated with behavioral and histological outcomes. Results: In comparison to unchallenged mice, Sert-/-/WD mutants, but not the WT/WD group, had increased locomotion and anxiety-like behavior, increased hepatic steatosis, and elevated expression of insulin receptor B and pro-inflammatory cytokines interleukin-1β (Il-1β) and Tnf, as well as decreased expression of leptin receptor B. The two genotypes displayed distinct gene expression patterns of nitric oxide (NO)-related molecules inducible NO synthase (iNos) and arginase (Arg2), insulin receptor-related signaling factors: cluster of differentiation 36 (Cd36), ecto-nucleotide pyrophosphatase/phosphodiesterase (Enpp), protein tyrosine phosphatase N1 (Ptpn1), cytochrome P450 omega-hydroxylase 4A14 (Cyp4a14), acyl-CoA synthetase 1 (Acsl1) and phosphatase and tensin homolog (Pten). Furthermore, there were profound differences in correlations between molecular, histological, and behavioral measurements across the two genotypes. Conclusions: Our findings suggest that the genetic deficiency of SERT results in abnormal hepatic pro-inflammatory and metabolic adaptations in response to WD. The significant correlations observed between behavioral measures and pro-inflammatory and metabolic alterations in WD-fed mice suggest the importance of liver-brain interactions and their role in the aberrant behaviors exhibited by Sert-/- mutants. This study presents the first evidence that altered liver functions are associated with pathological behaviors arising from genetic SERT deficiency.